Evaluation of the Growth Environment of a Hydrostatic Force Bioreactor for Preconditioning of Tissue−Engineered Constructs - Reinwald, Y; Leonard, K; Henstock, J; Whiteley, J; Osborne, J; Waters, S; Levesque, P; Haj, A (2014)
Bioreactors have been widely acknowledged as valuable tools to provide a growth environment for engineering tissues and to investigate the effect of physical forces on cells and cell-scaffold constructs. However, evaluation of the bioreactor environment during culture is critical to defining outcomes. In this study, the performance of a hydrostatic force bioreactor was examined by experimental measurements of changes in dissolved oxygen (O2), carbon dioxide (CO2), and pH after mechanical stimulation and the determination of physical forces (pressure and stress) in the bioreactor through mathematical modeling and numerical simulation. To determine the effect of hydrostatic pressure on bone formation, chick femur skeletal cell-seeded hydrogels were subjected to cyclic hydrostatic pressure at 0?270?kPa and 1?Hz for 1?h daily (5 days per week) over a period of 14 days. At the start of mechanical stimulation, dissolved O2 and CO2 in the medium increased and the pH of the medium decreased, but remained within human physiological ranges. Changes in physiological parameters (O2, CO2, and pH) were reversible when medium samples were placed in a standard cell culture incubator. In addition, computational modeling showed that the distribution and magnitude of physical forces depends on the shape and position of the cell-hydrogel constructs in the tissue culture format. Finally, hydrostatic pressure was seen to enhance mineralization of chick femur skeletal cell-seeded hydrogels.